Criminal Responsibility of the President of the United States of America - Mikić, Vladimir (NBP. Nauka, bezbednosti, policija, 2024)
Observed from a wider historical perspective, the most recent period of the constitutional life of the United States of America risks to be remembered as the one during which the presidential impeachment procedure was used incomparably more often than ever before. This sometimes attracts particular attention to the topic of criminal responsibility of the President, on which the Constitution itself remains silent. At the same time, legislation and jurisprudence seem to have been shying away from addressing this important and rather actual issue. The question whether the presidential immunity protects a sitting or a former president from arrest, trial, or punishment for deeds committed during the presidential term of office thus represents a particularly complex legal puzzler. This is particularly the case since the traditional checks-and-balances system appears to be displaying signs of weakness due to a overtly politicized procedure, notably in the absence of firm legal guidelines or clear theoretical perspectives.